Edible Cutlery Berbasis Pati Singkong dan Serat Ampas Tebu: Studi Literatur untuk Pengembangan Produk UMKM Berkelanjutan - Andi Nanda Nur Amriani F. MB.; Muhammad Ridwan; Pipi Diansari; Andi Syastiawan; Julianto Dwi Saputra (JASc (Journal of Agribusiness Sciences), 2026)
The geopolitical crisis in the Middle East that triggered the closure of the Strait of Hormuz has caused a surge in global plastic raw material prices by 45-80%, directly impacting culinary MSMEs in Indonesia. On the other hand, local resources such as cassava and sugarcane bagasse waste have not been optimally utilised as alternatives for environmentally friendly eating utensils. This study examines the potential development of edible cutlery based on cassava starch and sugarcane bagasse fiber as a technically and economically feasible alternative to plastic spoons for MSMEs in the context of the plastic price crisis and circular bioeconomy. A systematic literature review was conducted on Google Scholar, Scopus, and ScienceDirect databases (2015-2026) using keywords related to cassava starch, sugarcane bagasse, and edible cutlery. Out of 87 initial articles, 35 articles met the inclusion criteria and were analysed thematically. Cassava starch has an amylopectin content of 80-85%, which forms a strong structural matrix. Sugarcane bagasse fiber contains 40-50% cellulose with a tensile strength of 150-290 MPa. Based on literature synthesis, the recommended formulation is an 80:20 ratio (starch: fiber). The product is predicted to degrade within 45-60 days. With a selling price of Rp1,500-2,000/unit (cheaper than plastic spoons after the price increase), profit margins reach 46-59%. Cassava starch- and sugarcane bagasse fiber-based edible cutlery has the potential to be a more economical alternative to plastic spoons amidst the global increase in plastic prices, while also supporting a circular economy. Experimental validation is needed to confirm these predictive findings.